"Seniors only want respect": designing an oral health program for older adults. (4th January 2018) - Estrada, Ivette; Kunzel, Carol; Schrimshaw, Eric W.; Greenblatt, Ariel P.; Metcalf, Sara S.; Northridge, Mary E.
ABSTRACT: Aim: Persistent socioeconomic disparities in the oral disease burden contribute to pain and suffering among vulnerable and underserved populations who face systemic barriers to access oral health care, including older adults living in disadvantaged urban neighborhoods. The aim of this study is to gain the views of racial/ethnic minority older adults regarding what they believe would support them and their peers in visiting the dentist regularly. Methods and results: Focus groups were conducted and digitally audio‐recorded from 2013 to 2015 with 194 racial/ethnic minority women and men aged 50 years and older living in northern Manhattan who participated in one of 24 focus group sessions about improving oral health for older adults. Analysis of the transcripts was conducted using thematic content analysis. The majority of recommendations from racial/ethnic minority older adults to help older adults go to the dentist regularly were centered at the organization and provider level. The preeminence of respectful treatment to racial/ethnic minority older adults may be useful to underscore in oral health programs and settings. Conclusion: There is a need for greater engagement of and attention to patients and other stakeholders in developing, testing, and disseminating interventions to close the gaps in oral health care disparities.